PWE-091 Diagnostic yield in equivocal barium enemas: experience from a UK district general hospital. (23rd September 2015) - Isse, S; Krishnan, B; Sarwar, A; Subhani, J
Abstract : Introduction: Barium enema (BE) study is known to have a lower sensitivity 1 and specificity than colonoscopy but is often used in less fit patients or those with a lower risk of significant disease. A follow on colonoscopy is required either for therapy (ie, removal of a polyp) or clarification of "equivocal" radiological findings. The very anatomy (eg, marked diverticular disease) that leads to an equivocal BE may make the colonoscopy difficult or even dangerous. Further in anecdotal clinical practice few of these "equivocal" BE resulted in a proven pathology. The study assessed the yield of lower gastrointestinal endoscopy (LGE) used to clarify equivocal BE over a 12-month period at our institution. Methods: The list of all patients who had BE during a 12-month period was obtained from the radiology database. This was matched to patients who had a LGE in a 14-month period from the same start point. The extended period allowed for delays in arranging the LGE. Patients who had a LGE after the BE and whose indications included "equivocal" BE were identified. Their radiology and endoscopic reports were assessed for indications and findings. Results: 1381 BE were performed, and 2559 LGE. 139 patients in total were identified who had LGE following a BE. 44 of these patients had LGE due to an equivocal BE. Of these 44 patients two had no clinical indication on retrospective case review. A third (14/44) of the patients were over 70 years old. Of the 42 patients, 41 had normal findings at the area of suspicion (98%). One patient (2%) had a benign stricture confirmed on LGE but did not require any intervention. Furthermore, no cancers were detected, however, 4/44 (9.1%) had polyps not identified on the BE. In the remaining 95 patients who had LGE following a BE for other indications, primarily therapy or biopsies;polyps were identified in 34% and cancers in 13%. Conclusion: Very few BE required clarification of equivocal findings (42/1381) 3.0%, furthermore, definite abnormalities at BE had a high yield at subsequent LGE. Although this study was not designed to primarily assess the efficacy of BE it appears a useful investigation. Equivocal results on BE do not seem to be related to the suspicion of a lesion as much as a comment on the technical limitations of the study. Clinicians however seem to feel an equivocal result must require clarification. We would urge a different paradigm with review of the case and radiology prior to LGE. This may result in a reduction in these unnecessary procedures often in patients known to be at the greatest risk of complications (ie, over 70-year-olds).